The role and importance of teaching aids in the teaching and learning process, mathematics as a model - SAKHRI, Mohamed (Social Sciences Journal)
The topic of teaching methods preoccupied most of the active in the psychological and educational field’s interest due to its originality and it’s educational authenticity whereas many International Educational Systems head to both techniques and technology with the objective of linking the best learned with the newest educational methods to get out with a new high educational directrices that fit with the blast of knowledge that created a competition to make learning and teaching process exceptional . This paper was meant to highlight the important roles of the educational methods in learning as a core issue that inspires its research from the importance of educational act